Toxoid of Pseudomonas aeruginosa exotoxin A generated by deletion of an active-site residue. - Lukac, M (1988)
Glutamic acid-553 of Pseudomonas aeruginosa exotoxin A (ETA), identified previously as an active-site residue, was deleted by oligonucleotide-directed mutagenesis of the cloned toxin gene in Escherichia coli. The purified mutant toxin was stable, fully immunoreactive, and capable of blocking toxin receptors. ADP-ribosyltransferase and cytotoxic activities were at least 10(6)-fold lower than those of wild-type ETA, and injection of mice with 50 micrograms (equivalent to 400 lethal doses of ETA) produced no ill effects. The mutant toxin elicited high levels of neutralizing anti-ETA antibodies in mice, which protected against a challenge with 100 micrograms of authentic ETA (greater than 600 lethal doses). The mutant protein has the attributes of a toxoid and may be useful as a component of vaccines for individuals at risk for infection by P. aeruginosa.